Spiritual Emotional Freedom Technique (SEFT) and Time Management to Reduce Academic Stress in Students During The Covid-19 Pandemic - Muslim, Abdul Aziz; Tri Wahyuni (Indonesian Journal of Instructional Media and Model, 2023)
Academic stress is mental distress due to stressors related to the academic environment. The study of academic stress on adolescents and students has been extensively researched and has become a topic of great concern. Academic stress is mental distress due to academic stressors. Prolonged academic stress will not only affect the lives of adolescents but has the potential to reduce academic achievement. The research problem refers to the Spiritual Emotional Freedom Technique (SEFT) and whether time management can be used to reduce student academic stress. The research objective was to determine the effect of SEFT therapy and time management on reducing academic stress in students during the Covid-19 pandemic. This study used an experimental method to collect data and an experimental design that used a pretest - posttest control group design. The academic stress measurement tool uses the student - Life Stress Inventory (SSI). Data analysis using one way ANOVA. The results showed that there was an effect of the three experimental groups SEFT, time management, SEFT and time management on reducing academic stress in adolescents at school. This decrease has a higher score than the control group. SEFT has the greatest effect on reducing academic stress compared to all other experimental groups and the control group with a significance of 0.011.